APPLICATION OF THE «SMART CITY» CONCEPT IN THE IMPLEMENTATION OF THE PRINCIPLES OF SUSTAINABLE DEVELOPMENT OF TERRITORIAL COMMUNITIES - KINASH, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article aims to study the main components of the concept of "smart city", focusing on the features of its implementation in a specific territorial community. This concept serves as a tool that contributes to the sustainable development of territories. The implementation of the concept of "smart city" creates solutions that are able to solve the environmental, economic and social problems of our cities. It has been established that numerous cities around the world have adopted this concept. Its goal is to improve the well-being of citizens. The goal is achieved by improving the existing infrastructure to achieve the status of "smart city" or by actively seeking ways to adapt existing resources and networks. The city is transformed into "smart" through the use of various information computer technologies. These technologies are superimposed on each other: software, infrastructure and digital data. Sustainable development is important for meeting our current needs without sacrificing the ability of future generations to meet their own. Research materials indicate that more and more experts and researchers from different fields are working together to create solutions that will help solve environmental, economic and social problems to support the sustainable development of our cities. One of the tools that contributes to the sustainable development of territories is the concept of "smart city".The key definitions of the concept of "smart city" and its components are summarized. The characteristics of the outlined components are given. "Smart city" projects are considered using the example of one of the regional centers of Ukraine - the city of Ivano-Frankivsk. Here, the city authorities focused on the following aspects of implementing the studied concept: a service universe has been created, SMS-informing of the population is carried out, there is a feedback code, infographics are created, electronic queues operate, there are personal accounts of residents, various electronic services are provided. The most successful project of the city is "Transport". It is concluded that the application of the "smart city" concept through decentralized approaches in community management provides more effective management of important resources, urban dynamics and operations in real time and, thereby, contributes to the sustainable development of the territory.
Keywords: sustainable development; territorial communities; "smart city"; territorial development